Urban Consumerism in Karlo Sevilla’s Poems “Metro Manila Miasma” and “It’s Snowing in Manila” as An Ecological Critique of Anthropocentric Global Warming - Henrikus Joko Yulianto (Association for the Study of Literature and the Environment-Association of Southeast Asian Nations, 2022)
Journal of Southeast Asian Ecocriticism